Double-balloon Enteroscopy: The results of a new experience in Iran - Roushan, Nader (Iran University of Medical Sciences, 2014)
Background: Approach to the small intestine has been difficult even with newer methods. Double-balloon enteroscopy (DBE) has been created for diagnostic and therapeutic interventions in diseases of the small intestine. Small intestinal diseases have different etiologies in each country. The DBE has been introduced in recent years in Iran. Our aim was to study the indications and results of DBE in some academic centers in Iran. Methods: Fifty-five patients with symptoms and signs related to small intestine without definitive diagnosis but with previous workup were enrolled in the study. The DBE was performed in three different medical universities in Iran. Results: The mean age of the patients that underwent the DBE was 47.2 ± 17.3 years. Abdominal pain (54.5%) and occult gastrointestinal bleeding (23.6%) were the most common presentations. Small bowel lesions were detected in 26 patients (47.3%); the most common lesions were ulcer (46.2%) and polyps (19.2%). Crohn’s disease (12.7%) was the commonest diagnosis found in DBE procedure. Patients presenting with abdominal pain orl ower hemoglobin level were more likely to be diagnosed (both p≤ 0.05). Small intestinal diseases were ultimately diagnosed in 47.3% of the patients. Twenty percent of the patients had another disease outside the small bowel. Conclusions: DBE is an effective and relatively safe diagnostic and therapeutic option for small bowel evaluations. Accurate selection of patients and more experience technicians and physicians will improve the efficacy of this procedure in Iran.